A new e-health cloud-based system for cardiovascular risk assessment - Tatsis, G.; Baldoumas, G.; Christofilakis, V.; Kostarakis, P.; Varotsos, P. A.; Sarlis, N. V.; Skordas, E. S.; Bechlioulis, A.; Michalis, L. K.; Naka, K. K. (Frontiers in Electronics, 2023)
Sudden cardiac death (SCD) is one of the leading causes of death worldwide. Many individuals have no cardiovascular symptoms before the SCD event. As a result, the ability to identify the risk before such an event is extremely limited. Timely and accurate prediction of SCD using new electronic technologies is greatly needed. In this work, a new innovative e-health cloud-based system is presented that allows a stratification of SCD risk based on the method of natural time entropy variability analysis. This innovative, non-invasive system can be used easily in any setting. The e-health cloud-based system was evaluated using data from a total of 203 individuals, patients with chronic heart failure (CHF) who are at high risk of SCD and age-matched healthy controls. Statistical analysis was performed in two-time windows of different duration; the first-time window had a duration of 20 minutes, while the second was 10 minutes. Employing modern methods of machine learning, classifiers for the discrimination of CHF patients from the healthy controls were obtained for the first as well as the second (half-time) window. The results indicated a very good separation between the two groups, even from samples taken in a 10-minute time window. Larger studies are needed to further validate this novel e-health cloud-based system before its use in everyday clinical practice.